Socio-cultural Benefits of Curses and Blessings in South Wollo, Ethiopia (Global Journal of Human-Social Science, 2021)
The study was based on the socio-cultural significance of blessing and curses in Worailu Woreda, South Wollo Zone, Ethiopia. The main aim of this study was to study the origin of blessings and curses and to demonstrate in detail their benefits and purposes. Thus, the study could be a baseline as a starting point for researchers who want to study around the community, examine the interaction between blessing and curse, the sequence of performance as well as a detailed and in-depth look at the community's reaction to the subject. Both primary and secondary data sources were considered. The available data was analyzed by a functionalism approach. The finding showed that blessing and curse used to develop the moral law of the society used to shape the generation with humanity and ethics. The local community gives responsibility for the clan chiefs, religious leaders, and public figures to perform blessings and curses, and it has been believed that these individuals had relationship with the supernatural power (God). The finding confirmed that curses and blessing used by the people as conflict resolution in the study area. On the other hand, the study found that curses and blessings used to reflect and influence human emotions such as anxiety, fear, dismay, joy, and sadness.
Keywords: blessings; culture; curses; performance; socio-cultural benefits